Technique for Measuring Power across High Resistive Load of Triboelectric Energy Harvester - Subhawat Jayasvasti; Panu Thainiramit; Phonexai Yingyong; Don Isarakorn (My University, 2021)
This paper proposed a more-accurate-than-conventional measurement technique for determining electrical power across exceptionally high-impedance of triboelectric energy harvester (TEH). The key idea of this proposed technique was to measure the voltage across an introduced, parallelly-connected resistor divider to the oscilloscope instead of the voltage across the harvester. An experiment was set up to verify the measurement accuracy performance of this technique against the ideal theoretical values. The maximum percentage error found was only 2.30%, while the conventional measurement technique could not be used to measure voltage across high impedance TEH at all because the readings were not accurate, i.e., the measurement error would be at least over 10%. Therefore, we concluded that this proposed technique should always be used instead of the conventional measurement technique for power measurement of any TEH. A suggestion that we would like to offer to researchers investigating or developing a TEH is that, in using our measurement technique, a good starting point for a load to probe resistance ratio is 1:10, a ratio that worked well for our TEH test bench that we developed.
Keywords: Resistive touchscreen; Multimeter; Accuracy and precision; Advanced Sensor and Energy Harvesting Materials